Artistic representation of reality in the stories of Huseynbala Miralamov (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The stories in the creativity of Huseynbala Miralamov, the well-known representative of contemporary Azerbaijani literature, is analyzed in this article. Here stories of the writer is studied in the context of the modern life realities, the problems of human and time are invloved to the analysis in the aspect of human factor and unique approach to events. Realization problems of the life realities, presentation of spiritual world of human in the moral and psychological character are paid special attention in the prose of H. Miralamov in this article.
Keywords: Huseynbala Miralamov; artistic praise; realty; human; time